PENGARUH PEMBERIAN PAKAN CAMPURAN TEPUNG DAUN KELOR (Moringa oleifera L.) DAN DEDAK PADI TERHADAP PERTUMBUHAN IKAN LELE (Clarias sp.) SEBAGAI SUMBER BELAJAR BIOLOGI - Indriyani Putri; Agus Sutanto; Suharno Zen (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2021)
As the price of pellet mills increases, the use of natural ingredients that are rich in nutrients is expected to be used in making feed mixes with low consideration, available at any time, easily available, and have good nutritional content to reduce the high cost of feed. Making the mixture feeding of Moringa powder (Moringa oleifera L) and rice bran aims to see the effect of the feed on the catfish growth (Clarias sp), find out the best variation of the mixture, and know the results of this study can be used as a source of biology learning. This research is an experiment, using a Completely Randomized Design (CRD) with 1 control, 3 treatments, and 6 replications, with P0: Control, P1: mixture feeding treatment of 2% Moringa leaf flour and rice bran, P2: mixture feeding treatment of 3% Moringa leaf flour and rice bran, P3: mixture feeding treatment of 4% Moringa leaf flour and rice bran. Based on the research result it can be concluded that there is an increase in absolute weight and absolute length in catfish, with the research result of the average absolute weight P0 = 19.72, P1 = 23.61, P2 = 33.33, P3 = 38.05 and the results of average absolute length P0 = 6.16, P1 = 7.11, P2 = 8.08, P3 = 10.14. The results of this study can be used as a source of learning biology in the form of posters on growth and development material for high school at XII grade. The results of the validation of learning resources by material and design experts concluded that the poster made by the researcher was appropriate to be used as a learning resource with an average score of material experts was 94 and design experts was 94.